AB0550 Hughes-Stovin Syndrome: Successful Use of Infliximab in Life Threatening Behcet's, with Pulmonary Involvement in 3 Cases in An University Hospital. (15th July 2016) - Prathapsingh, M.; Bagguley, S.; Jones, S.; Hope-Gill, B.; Gordon, A.; Nash, J.T.
Abstract : Background: Hughes-Stovin Syndrome (HSS) is described as a very rare vascular manifestation of Behcet's disease in medical literature. HSS is a very rare clinical disorder and around 40–60 published cases of HSS have been described in medical literature so far. Objectives: To illustrate the use of Infliximab in three cases. Methods: Case1: A 25 year old male presented with optic nerve emboli, oral ulcers and CT scan revealed pulmonary artery aneurysms within the right lower lobe and pulmonary emboli (image). This was treated with Endovascular coiling, pulsed cyclophosphamide, mycophenolate and prednisolone. He had ongoing episodes of haemoptysis that were treated with Infliximab. The patient is now well controlled on Infliximab, mycophenolate and prednisolone. Case2: A 34 year old male with history of genital and mouth ulcers, presented with haemoptysis and CT scan showed multiple pulmonary emboli with aneurysms. He was treated with pulsed Methyl-prednisolone and infliximab 5mg /kg at weeks 0, 4, 6 and 8, followed by every 8 weeks and Methotrexate. He later developed a DVT, therefore the methotrexate was switched to Azathioprine 2.5mg/kg/day and he received Methyl-prednisolone. Infliximab dose was increased to every 2 weeks. After ongoing review he was switched from Infliximab to Adalimumab and he is now in remission. Case3: A 19 year old male admitted with haemoptysis and respiratory compromise and was intubated in ICU. His CTPA showed bilateral pulmonary emboli with aneurysms. He had erythematous macules, follicular papules, oral ulcers and weight loss with positive pathergy. He was treated with IV methyl prednisolone and infliximab 5mg/kg every 2 weeks.He was extubated 24 hrs after starting treatment and he was discharged home within 9 days of treatment.He is maintained on Adalimumab and Azathioprine and he is now in remission. Results: Although case 1 did not fulfill the ISG criteria for Behcet's disease, case 2&3 fulfilled the criteria. Case1 had a protracted course although managed as per Behcet's pathway by Behcet's centres of excellence in UK and Infliximab was used as a step up treatment. Case 3 presented very unwell, but he was extubated 24 hrs after starting treatment and Infliximab was used as an induction treatment. Conclusions: Early diagnosis and timely intervention is crucial in improving the prognosis of patients with HSS. Our experience of these 3 rare cases suggests that Infliximab should be used as induction treatment in managing life threatening HSS. References: Orphanet J Rare Dis. 2011 Apr 13;6:15. doi: 10.1186/1750-1172-6-15. Review.Hughes-Stovin syndrome. Khalid U, Saleem T. Oman Med J. 2015 Jan;30(1):59–62. doi: 10.5001/omj.2015.11.Hughes-stovin syndrome and massive hemoptysis: a management challenge.Al-Zeedy K, Jayakrishnan B, Rizavi D, Alkaabi J Clin Pract. 2014 Nov 6;4(3):647. doi: 10.4081/cp.2014.647. eCollection 2014 Oct 30. Moderate hemoptysis caused by hughes-stovin syndrome. El Aoud S, Frikha F, Snoussi M, Bahloul Z. Disclosure of Interest: None declared